Fearful symmetry: Is God a Geometer? - Stewart, Ian; Golubitsky, Martin (Penguin Books, 1992)
Symmetry is one of the most powerful and wide-ranging of mathematical ideas with recent work on symmetry breaking, when symmetrical patterns are slightly altered or corrupted, throwing up an extraordinary range of applications and natural examples, from the stripes on a tiger\'s back to the territorial patterns of fish and to the structure of viruses. This book looks at the applications of symmetry and symmetry breaking to subjects as diverse as weather patterns, crystal structures, the buckling of beams and particle physics.